Motivasi Ibu Rumah Tangga Belajar Bahasa Arab dan Pengaruhnya Dalam Mempelajari Al-Quran (Studi Kasus Ibu Rumah Tangga Mustawa Tsalits Mahad Abu Bakar Ash-Shiddiq Universitas Muhammadiyah Surakarta Tahun Pelajaran 2015-2016) - Shofiyani, Anisa Fitri, Dr. Ari Anshori, M.Ag, Dr. Mutohharun Jinan, M.Ag (2016)
This research has aims to describe the motivation of housewives in learning Arabic in Ma'had Abu Bakar and to know deeply the influencing of learning Arabic in understanding Qur'an. The type of research used by the writer is field research, that is qualitative research. The approach was used is psychological approaches. This research was done in Ma'had Abu Bakar Muhammadiyah University of Surakarta. The writer used observation, interviews, and documentation as the method of collecting the data. Where as, the data analysis of this research includes data reduction, data presentation and drawing conclusion. The validity of the data have been tested by triangulation techniques. The conclusion of the research is that housewives who learn Arabic in Ma'had Abu Bakar is divided into two categories. Firstly, housewive who has an intrinsic motivation. Secondly, housewive who has an extrinsic motivation. The intrinsic motivation in learning Arabic in Ma'had Abu Bakar are: 1) Passion or willingness to success in learning Arabic, 2) Motivation and need to success in learning Arabic, 3) Hope and prospects of their future. While, the extrinsic motivation includes suggestion and motivation from the teachers, motivation from husbands, reward in learning, conducive and enjoy learning nvironment, and intensive learning process which makes easier in mastering Arabic language. The influencing of learning Arabic in understanding Qur'an are: 1) The influencing in reading Qur'an with a proper pronunciation and tajwid. 2) The influence in interpretation of Qur'an is to make easier in understanding it. 3) The influence in memorizing Qur'an is to make easier in memorizing.